EXPLORATION OF CREATIVITY THROUGH EMPOWERMENT ACTIVITIES TIE DYE MAKING USING A COOPERATIVE LEARNING APPROACH FOR ELEMENTARY STUDENTS - Kurniastuti, Dina; Susanto, Moh. Rusnoto; Arumsari, Mela Dina; Selimanorita, Shafa` (International Journal of Engagement and Empowerment (IJE2), 2023)
Exploratory activities through empowering the creation of Tie Dye works in practical Arts, Culture and Crafts (SBdP) learning can improve various character values in students. Some of the characters that can be developed are love of art and culture, love of the homeland, responsibility and cooperation. This competency empowerment activity aims to reveal the development of cooperative character through the SBdP practice of making jumputan or tie dye batik. This article is a process of community service carried out in the school environment using a participatory approach, using joint data collection techniques in activities and empowerment through observation and peer review. The subjects were 18 grade 5 students at Klaci State Elementary School. Data obtained directly in the field when practice is reduced to sorting, selecting and simplifying subject matter, then the appropriate data will be presented through analytical exposure in a phenomenological perspective. Competency exploration and empowerment activities carried out on May 17 2023 at SD Negeri Klaci through the practice of making batik and Tie Dye with a cooperative learning approach can develop the character of cooperation through the steps of making and group work carried out